'Proximity logistics': Characterizing the development of logistics facilities in dense, mixed-use urban areas around the world. (December 2022) - Buldeo Rai, Heleen; Kang, Sanggyun; Sakai, Takanori; Tejada, Carla; Yuan, Quan (Jack); Conway, Alison; Dablanc, Laetitia
Abstract: The maturation of digital(ized) consumption, together with the amplification of cities' initiatives in response to local and global environmental challenges, has placed goods transport, an essential but impactful activity, at the forefront of urban stakeholders' scrutiny. High-performance and low-impact supply chains benefit from the presence of logistics facilities in proximity to goods' destinations. This development of logistics facilities in high-demand areas, which are essentially urban, dense and mixed-use, we term 'proximity logistics'. It is the focus of this article. Proximity logistics entails extending and refining networks of logistics facilities towards urban cores and allows them to counteract some of the undesirable effects that their historic tendency to outward migration (or logistics sprawl) potentially brings about. The phenomenon is established around the world, albeit to different extents. In this article, we discuss the trends supporting proximity logistics' development and present a typology of facilities it could entail, followed by case studies of five cities: New York (United States); Paris (France); Seoul (South Korea); Shanghai (China); and Tokyo (Japan). We characterize the state of practice of logistics facilities in each city's dense, mixed-use areas, compare the characteristics in light of their context and distill learnings in support of sustainable land use patterns.